Activation of apoptotic cell death by skin mucus from Asian swamp eel (Monopterus albus) against human lung cancer cell line - Mahmood, Syed; Hilles, AYAH (Sultan Qaboos University, Oman, 2019)
Abstract. Asian swamp eel (Monopterus albus) is a freshwater fish which distributed widely in the East of India mainly across Malay Peninsula and Indochinese Peninsula, it is also broadly distributed in the Southern areas of East Asia including, southeastern China, Western Japanese Archipelago, and Korean Peninsula. It lives in muddy places, rice paddies, and slow-flowing currents areas. It has a unique morphological elongated body which is similar to snake and covered with a thick layer of mucus. The objective of this study is to screen the cytotoxic activity of eel skin mucus extracts and to evaluate the mechanism of cell death apoptosis or necrosis based on caspases activity assays. For this purpose eel skin mucus was collected from healthy fresh eels to prepare aqueous and methanol extracts. Preliminary cytotoxicity study was demonstrated against Non-small-cell lung carcinoma cell line (A549) using cell viability assay which revealed that methanol extract was more potent than aqueous extract based on the response of ESM methanol and aqueous extracts to the relevant IC50 concentrations as IC50 values were 621±0.09 µg/mL and 845 ± 0.25 µg/mL respectively. Subsequently cell death was induced through triggering apoptosis by the activation of caspase-3/7, 8 and 9. In conclusion, the present study has revealed the cytotoxic potentials of eel skin mucus which may lead to the development of new anticancer agents. Keywords: Monopterus albus; cytotoxic activity; apoptosis; caspases